Neuraminidase-mediated haemagglutination of recent human influenza A(H3N2) viruses is determined by arginine 150 flanking the neuraminidase catalytic site - Mögling, Ramona; Richard, Mathilde J.; Vliet, Stefan van der; Beek, Ruud van; Schrauwen, Eefje J. A.; Spronken, Monique I.; Rimmelzwaan, Guus F.; Fouchier, Ron A. M. (Journal of general virology, 2017)
Over the last decade, an increasing proportion of circulating human influenza A(H3N2) viruses exhibited haemagglutination activity that was sensitive to neuraminidase inhibitors. This change in haemagglutination as compared to older circulating A(H3N2) viruses prompted an investigation of the underlying molecular basis. Recent human influenza A(H3N2) viruses were found to agglutinate turkey erythrocytes in a manner that could be blocked with either oseltamivir or neuraminidase-specific antisera, indicating that agglutination was driven by neuraminidase, with a low or negligible contribution of haemagglutinin. Using representative virus recombinants it was shown that the haemagglutinin of a recent A(H3N2) virus indeed had decreased activity to agglutinate turkey erythrocytes, while its neuraminidase displayed increased haemagglutinating activity. Viruses with chimeric and mutant neuraminidases were used to identify the amino acid substitution histidine to arginine at position 150 flanking the neuraminidase catalytic site as the determinant of this neuraminidase-mediated haemagglutination. An analysis of publicly available neuraminidase gene sequences showed that viruses with histidine at position 150 were rapidly replaced by viruses with arginine at this position between 2005 and 2008, in agreement with the phenotypic data. As a consequence of neuraminidase-mediated haemagglutination of recent A(H3N2) viruses and poor haemagglutination via haemagglutinin, haemagglutination inhibition assays with A(H3N2) antisera are no longer useful to characterize the antigenic properties of the haemagglutinin of these viruses for vaccine strain selection purposes. Continuous monitoring of the evolution of these viruses and potential consequences for vaccine strain selection remains important.